Innovative STEM-Excel Integration to Foster Students' Mathematical Representation Skills ? - Zulfadli Zulfadli; Evendi Evendi; Ibnu Khaldun; Taufik Taufik; Putri Nabilah (Jurnal Pemberdayaan Masyarakat, 2026)
Mathematical representation ability (MRA) is essential to mathematics learning, yet many high school students struggle with topics such as quadratic equations and functions. This study aims to develop and evaluate an Excel spreadsheet–based learning media integrated with a STEM (Science, Technology, Engineering, Mathematics) approach to enhance students' MRA. Using the Research and Development (RD) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the media was tested on 32 tenth-grade students at SMA Negeri 1 Samalanga. Data were collected through expert validation, teacher and student questionnaires, and pretest-posttest MRA instruments. The results showed that the media achieved high validity (89.25%), was rated very practical by teachers (83.2%) and students (87.3%), and significantly improved students' MRA, with an N-Gain score of 0.75 (high category). Thus, the Excel-STEM learning media is valid, practical, and effective in improving students' mathematical representation skills. This study contributes to the field of educational technology by offering a low-cost, accessible, and pedagogically sound digital tool that integrates STEM principles into mathematics instruction, supporting the development of representational fluency in secondary education.